2016
DOI: 10.1371/journal.pone.0156636
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human α-Lactalbumin Gene Insertion into the Goat β-Lactoglobulin Locus by TALEN-Mediated Homologous Recombination

Abstract: Special value of goat milk in human nutrition and well being is associated with medical problems of food allergies which are caused by milk proteins such as β-lactoglobulin (BLG). Here, we employed transcription activator-like effector nuclease (TALEN)-assisted homologous recombination in goat fibroblasts to introduce human α-lactalbumin (hLA) genes into goat BLG locus. TALEN-mediated targeting enabled isolation of colonies with mono- and bi-allelic transgene integration in up to 10.1% and 1.1%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This initial report presented the potential of the TALEN endonucleases for the introduction of desirable allelic introgressions into the genomes of farm animals. TALENs have also been applied in goats to target the BLG gene (Cui et al, 2015; Ge et al, 2016; Zhu et al, 2016b; Yuan et al, 2017). Furthermore, gene-edited goats that carry both BLG knockout and enriched expression of human lactoferrin (hLF) (Cui et al, 2015) or human α-lactalbumin (hLA) (Zhu et al, 2016b) have been generated using SCNT.…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial report presented the potential of the TALEN endonucleases for the introduction of desirable allelic introgressions into the genomes of farm animals. TALENs have also been applied in goats to target the BLG gene (Cui et al, 2015; Ge et al, 2016; Zhu et al, 2016b; Yuan et al, 2017). Furthermore, gene-edited goats that carry both BLG knockout and enriched expression of human lactoferrin (hLF) (Cui et al, 2015) or human α-lactalbumin (hLA) (Zhu et al, 2016b) have been generated using SCNT.…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…Furthermore, Zhu et al reported the generation of BLG knockout goats with enriched expression of hLA in milk, six live births were obtained, one was a biallelic targeted goat (which died after 1 month), and the other five goats were BLG hLA/+ . BLG expression in the milk of transgenic goats was reduced, while hLA was highly expressed compared to normal goats (Zhu et al, 2016b). Caprine MSTN knockout using TALENs has also been reported.…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…The emphasis on this study, however, was on the high level expression of human serum albumin for further purification from milk and not at using the BLG-free, human serum albumin-rich milk as food. Similarly, BLG knockout combining TALENs-mediated gene editing and SCNT was also performed in goats and resulted in targeted mono- and bi-allelic gene exchange of BLG against either human lactoferrin (hLf) or human alpha-lactalbumin (hLA) 7 , 8 . Biallelically targeted BLG hLf/hLf goats were shown to no longer produce BLG but high levels of hLf 8 , whereas monoallelically targeted BLG +/hLA goats exhibited slightly reduced BLG and high expression of hLA 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The TALEN-mediated system was also used to knockout the BLG gene to reduce allergens and to create a knockin of human lactoferrin (hLF) for practical use as a bioreactor (Cui et al, 2015). Furthermore, targeting exon 1 of the BLG locus has been efficiently applied (Zhu et al, 2016). Goat MSTN gene editing has also been examined using the TALEN-mediated system (Yu et al, 2016).…”
Section: Goatmentioning
confidence: 99%